African cattle genetic resources: Their unique attributes and conservation through utilization for milk production - Kahi, A.K.; Rege, J.E.O. (Utrecht University, 2001)
Ensuring that locally adopted breeds are a functional part of production systems is the most national and sustainable way to conserve animal genetic resources. This can only be possible if sustainable breeding strategies for such animals are developed which take into account their economically important and unique attributes. African cattle genetic resources are owned by small-scale farmers and pastoralists for whom they are a source for improved nutrition, income and a secure form of investment. Their conservation therefore, should be through utilization if they are to be of any benefit to these farmers and pastoralists. This discussion focuses on five very pertinent questions that need to be answered if the conservation of African cattle genetic resources is to be effective and sustainable: what, why and who should we conserve? and who are the stakeholders and what are their roles in conservation efforts?